Usage of Buy Now Pay Later, Hedonic Motivation, and Impulse Buying among Gen Z in E-Commerce Shopee - Doni Susanto; Muhammad Willy Apriza; Tiara Muthiarsih (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The purpose of this research is to determine the influence of Buy Now Pay Later (BNPL) and hedonic motivation on the impulsive buying behavior of Gen Z on e-commerce platforms, specifically Shopee. Previous studies have shown that the use of BNPL has a positive effect on impulsive buying behavior. Other studies have also shown that hedonic motivation positively impacts impulsive buying. The research methodology employs an inferential quantitative approach to collect primary data from 100 Gen Z respondents who use Shopee e-commerce through the distribution of questionnaires. The data analysis technique used is Structural Equation Modeling (SEM) with SmartPLS 4. The main findings of this study indicate that BNPL positively affects impulsive buying. Hedonic motivation also positively influences the impulsive buying behavior of Gen Z on e-commerce, specifically Shopee. These results contribute to understanding the factors influencing Gen Z's impulsive buying behavior and the impact of BNPL usage and hedonic motivation on consumer impulsive buying behavior. Therefore, this research contributes to expanding knowledge about the factors affecting impulsive buying behavior of Generation Z on e-commerce platforms.